QUANTITATIVE DIFFERENCES IN MORPHOLOGICAL AND POSTURAL STATUS BETWEEN GIRLS AND CHILDREN OF PRIMARY UPBRINGING AND EDUCATION - Dževad Džibrić; Alema Talović; Rijad Novaković; Admir Hadžikadunić (Sport Scientific And Practical Aspects, 2025)
On a sample of 405 examinees, males and females from the first to the fifth grade of elementary school, a system of sixteen variables (8 morphological and 8 variables for assessing postural status) was applied to determine the differences between boys and girls. The results have shown that there are statistically significant differences in body weight and body mass index between boys and girls of the second, third, fourth and fifth grade among the examined samples. The differences in variables for the evaluation of skin folds exist, but not as much as in these two previous variables. The most pronounced differences in body holding are presented in the variable shape (development) of the thorax and are recorded among the first, second, third and fifth-grade subjects. There are differences in the grade of the head in the first grade and in the evaluation of blades holding in the first and fourth grade. The obtained information on the differences in treated variables should provide a basis for the application of certain motor and functional tests to an optimal plan, program, and operationalize the teaching of physical and medical education, as well as to control the development of primary anthropological features under the influence of the standard programmed gender content.